Enhanced Control of a Series-Parallel Modular Multilevel Converter for Vehicle-To-Grid Fast Charging Applications - Espina-Gonzalez, E; Diaz-Diaz, M; Ravet-Orellana, T (Institute of Electrical and Electronics Engineers Inc., 2023)
The fast and flexible Electric Vehicle Supply Equiment (EVSE) requirement has increased as electromobility is massifed. Currently, high-power EVSE are reaching the 1 MW barrier, and, consequently, novel power converter topologies have been introduced as an alternative to the traditional dual active bridge-based EVSE. This paper proposes an enhanced control of a Series-Parallel Modular Multilevel Converter (MMC) based EVSE for fast and multiple electric vehicle charging applications. The proposed converter is regulated using standard decoupled MMC control strategies designed to provide Vehicle-to-Grid (V2G) capabilities. Simulation results are presented using a 500 kW model developed in PLECS to validate the proposed topology and control systems. Unlike previous research, these results demonstrate bidirectional power flow and support multiple port charging. © 2023 IEEE.